„Es wolt vns Gott genedig sein“: Eine „Straßburger“ Melodie aus Wittenberg - Ameln, Konrad (Jahrbuch für Liturgik und Hymnologie, 1989)
A single printed sheet from Hans Knappe, Magdeburg 1524, is the oldest authenticated document of the hymn "Es wolle Gott uns gnädig sein". This printed sheet of rather insufficient quality will hardly be the pattern for the Strasbourg printings 1524/1525. In all probability the single Magdeburg paper and those Strasbourg printings derive from another document in mensura-notation. M. Greiter cannot be seen being the author of the tune; this is proved by stylistic inquiries and the context of the origins. There are certain indications for Luther, being the author. A reconstruction of the original pattern might be possible by comparing the Magdeburg document with later printings. You can find characteristic variations of this original form within the later tradition.